Photocatalytic Activity of ZnO Nanoparticles Synthesized Using Persea sp. Leaf Extract Toward Methylene Blue Dye Degradation - Simbolon, Ryanna Nathania; Yanti, Demi Dama; I Putu Mahendra; Aditya Ayuwulanda; Rahmat Kurniawan; Cindy Moyna Clara L. A.; Tuta, Gabriell Vannes Sabat (Universitas Islam Indonesia, 2025)
Methylene blue dye is widely used in various industries, but improper disposal can severely harm aquatic ecosystems. Zinc oxide (ZnO), a well-known semiconductor, is frequently employed to degrade dye pollutants in aqueous media. This study synthesized ZnO nanoparticles via a precipitation method incorporating a green synthesis approach, utilizing Persea sp (Persea sp.) leaf extract as an eco-friendly alternative to synthetic chemical reagents. Persea sp leaves contain diverse secondary metabolites, including saponins, alkaloids, tannins, flavonoids, and phenolics, which act as capping agents during water-based synthesis. Characterization was conducted using X-ray diffraction (XRD), UV–visible diffuse reflectance spectroscopy (UV-DRS), and scanning electron microscopy (SEM). The photocatalytic activity of the ZnO nanoparticles toward methylene blue degradation was evaluated under UV irradiation at time intervals of 10, 20, 30, 40, 50, and 60 minutes. UV-DRS results indicated a maximum absorption wavelength of 364 nm with a band gap energy of 3.26 eV. XRD analysis confirmed a hexagonal wurtzite structure (JCPDS no. 36-1451) with an average crystallite size of 21.24 nm. SEM imaging revealed a nanospherical morphology with an average particle size of 79.28 nm. The synthesized ZnO nanoparticles achieved 61.77% degradation efficiency for 5 ppm methylene blue. These findings demonstrate that green-synthesized ZnO nanoparticles from Persea sp. leaf have promising potential as sustainable photocatalysts for dye removal, contributing to the development of environmentally friendly wastewater treatment technologies